Strand 2: A learning, assessing, and evaluating environment for asynchronous Web-based courses - Barker, Keith; McCartney, Robert; Wurst, Karl; Weiner, Bob; Lancor, Lisa (Proceedings of the International Conference on Networked Learning, 1998)
A methodology for web-based learning in engineering has been developed and offers an environment for educators to deliver hypermedia information in a controlled and structured way. The appropriate design of this environment was of paramount importance so that the student could navigate it in a simple and efficient manner. The system provides feedback to the student for learning assessment and feedback to the instructor and curriculum originator for course improvement. This environment has been uriliz.cd over 4 semesters to support the learning in a digital logic design laboratory. It has provided essential and supplementary material including animations, video, simulation, as well as text and graphic information.